The effect of Sharia Purposes on Permissions: An applied Jurisprudence Study - Ali, Ramadan Hamdoon (Journal of Tikrit University for Humanities, 2020)
The study of the purposes of sharia has a great deal of invistigations. Moreover, it has a great expansion in contemporary studies. Scholars in their researches almost covered all its aspects. This gives importance of this science. However, there are some aspects that have not received the researchers’ attention like the presence of purposes in the aspects of rulings. One of these purposes is how do we imagine that there is a purpose in fasting legislation or in the rituals of Hajj and so on. The research presented the truth of the "effect, purposes, and permissions" and even the permissions in Islamic law were collected in the "schedule" It gives a scientific dimension to a serious attempt to redraw the curricula of Islamic law sciences, especially in matters that did not obtain a presence in postgraduate studies.